The Implementation of Songs in Teaching English for Young Learners in Online Learning Context - Putri, Made Willynda; Juniarta, Putu Adi Krisna; Wahyuni, Luh Gede Eka (The Art of Teaching English as a Foreign Language (TATEFL), 2022)
The purpose of this study was to describe the implementation of song in teaching speaking competency as well as problems encountered by teachers during the implementation at SD N 2 Tembok, Buleleng Regency. Researchers collected data in a qualitative way, through interviews and observation. Then, the data were analyzed through 3 processes proposed by Dull & Reinhardt (2014). The purpose of implementing song in all stages in learning is to make students adapted with the English vocabulary and pronunciation by using fun method which is via song which is familiar for the students. Based on the result of this study, it can be concluded that the teacher basically implemented the song to the learning in three activities such as opening activity, whilst activity and closing activity by giving the link of youtube video to the students as well as helping them in translation to encourage the students to learning to speak English by using song. The problem that mostly occurred in the class to teach song for speaking English was internet connection due to online class caused of covid-19 pandemic. Because of that, doing voice recording is needed for the students to check their grammar as well as their pronunciation.